Early Morbidity and Outcome After Clipping Versus Coiling of Anterior Communicating Artery Aneurysms: A Head-to-Head Analysis - Wajid, Abdul; Ahmad, Usman; Cheema, Nabeel Ashraf; Nasir, Hammad; John, Anosh; Asif, Tehreem (Journal of Rawalpindi Medical College, 2026)
Objective: Intracranial aneurysms are pathological enlargements of intracranial arteries that frequently manifest at the arterial branching sites. Surgical intervention of the anterior communicating artery aneurysm may present technical difficulties due to its irregular anatomical configuration, intricate hemodynamics, and unfavorable morphology that hinders successful clipping. Another method of treatment is endovascular coiling of an aneurysm. Both treatment modalities are complementary rather than competitive due to their respective strengths and limitations. This study aims to compare the two treatment modalities. Methods: This study was conducted to get the local evidence and implement the results of this study to reduce complications and improve the outcome of surgery. So, this experimental study was done at the Department of Neurosurgery, Punjab Institute of Neurosciences, Lahore, for 12 months. Sample size of 60 cases; 30 cases in each group were included through Non-Probability Consecutive sampling. Group A patients were subjected to clipping-based surgery. Patients in group B underwent an endovascular procedure utilizing coiling. Patients were observed for mortality and complications during stay in hospital, and the outcome of 3 months follow up. Results: Patients who underwent clipping had a significantly higher rate of favorable outcomes (23 out of 30; 76.7%) compared to those who underwent Coiling (7 out of 30; 23.3%). Conclusion: Surgical clipping carries a promising treatment option for anterior communicating artery aneurysm with good long-term prognosis compared to endovascular clipping. Clipping carries a higher risk of some complications, such as surgical site infection, meningitis, and CSF leak. In contrast, endovascular coiling carries higher mortality and morbidity, with a higher rate of focal neurological deficits and poorer prognosis. Keywords: Intracranial aneurysm, anterior communicating artery aneurysm, embolization, therapeutic, neurosurgical procedures, microsurgery.